Wind energy conversion system based on DFIG using three-phase AC-AC matrix converter - Fatima-ezzahra Blouh; Basma Boujidi; Mohamed Bezza (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Due to the development of power electronics technology, the use of a new generation of power converter AC-AC matrix converters has received special attention, which provides direct power converter AC-AC, bidirectional power flow, near-sinusoidal input, and output waveforms. The performance analysis of a variable-speed wind turbine based on a doubly fed induction generator and connected to the main grid through a three-phase matrix converter is presented in this paper. Additionally, this paper proposes the utilization of a space vector modulation approach in the three-phase matrix converter. Other benefits of the space vector modulation approach include lower total harmonic distortion of output voltage and lower switching loss. The simulation analysis of the proposed power conversion system using MATLAB/Simulink/SimPowerSystems toolbox R2021a is presented in this paper.